Laminated glass and method for producing the same
Patent Information
- Application Number
- CN202410397314.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-03
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-04-03
AI Technical Summary
[0003]目前,汽车前挡风玻璃通常由2层2mm~3mm厚的钠钙玻璃与1层0.3mm~0.7mm厚的有机胶层组成,总厚度达5mm~6mm,其无法满足汽车轻量化的要求
[0024]本发明通过对铝硅酸盐玻璃的组成原料进行优化,使制备得到的铝硅酸盐玻璃具有与钠钙玻璃相近的热学性能,二者在加热时能够弯曲至相同的形状。本发明将上述的铝硅酸盐玻璃与钠钙玻璃组合,极大地减小了夹层玻璃的总厚度和总重量,实现了汽车玻璃轻量化和安全化的要求。
Smart Images

Figure CN118219630B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of glass product technology, and in particular to a laminated glass and its preparation method. Background Technology
[0002] With the development and progress of science and technology, improving the utilization efficiency of energy sources such as gasoline fuel and electricity in automobiles and pursuing lightweight automotive components are future development trends.
[0003] Currently, automotive windshields typically consist of two layers of 2mm-3mm thick soda-lime glass and one layer of 0.3mm-0.7mm thick organic adhesive, totaling 5mm-6mm in thickness, which fails to meet the requirements for lightweight automotive construction. To reduce the weight of automotive glass, the interior glass pane is made thinner, resulting in reduced rigidity. However, during the glass heating and bending process, the different compositions of the two glass layers lead to differences in their softening points, and thinner glass is more prone to bending and deformation than thicker glass. These factors make it difficult to bend them into the same shape, resulting in difficulties in bonding the two layers together.
[0004] Therefore, traditional technologies still need improvement. Summary of the Invention
[0005] Based on this, the present invention provides a laminated glass that meets the requirements of automotive safety and lightweighting, and a method for preparing the same. Specific technical solutions include:
[0006] According to one aspect of the present invention, a laminated glass is provided, comprising soda-lime glass, an adhesive layer, and chemically tempered aluminosilicate glass stacked sequentially, wherein the thickness of the chemically tempered aluminosilicate glass is less than the thickness of the soda-lime glass; the difference between the annealing temperature of the chemically tempered aluminosilicate glass and the soda-lime glass is -16°C to 16°C, the difference between their softening temperature and their transition temperature is -25°C to 25°C, and the difference between their transition temperatures is -25°C to 25°C.
[0007] The chemically tempered aluminosilicate glass is obtained by tempering aluminosilicate glass, which comprises the following raw materials: SiO2 55wt%~66wt%, Al2O3 9wt%~15wt%, Na2O 11wt%~16wt%, K2O 4wt%~8wt%, MgO 1wt%~5wt%, B2O3 1wt%~6wt%, and ZrO2 0.2wt%~2wt%; wherein, the mass percentage of Al2O3 is a, the sum of the mass percentages of K2O and B2O3 is b, and 1.24≤a / b≤1.67.
[0008] In one embodiment, the aluminosilicate glass comprises the following raw materials: SiO2 57wt%~62wt%, Al2O3 12.5wt%~15wt%, Na2O 13.4wt%~16wt%, K2O 6.5wt%~7.5wt%, MgO 1.6wt%~3.7wt%, B2O3 1wt%~2wt%, and ZrO2 1.1wt%~1.7wt%.
[0009] In one embodiment, the difference in annealing temperature between the chemically tempered aluminosilicate glass and the soda-lime glass is -4°C to 4°C, optionally -3°C to 3°C, optionally -2°C to 2°C, or optionally -1°C to 1°C; and / or
[0010] The difference in softening point temperature between the chemically tempered aluminosilicate glass and the soda-lime glass is -4℃ to 4℃, optionally -3℃ to 3℃, optionally -2℃ to 2℃, or optionally -1℃ to 1℃; and / or
[0011] The temperature difference between the transition point of the chemically tempered aluminosilicate glass and the soda-lime glass is -4℃ to 4℃, and can be selected as -3℃ to 3℃, -2℃ to 2℃, or -1℃ to 1℃.
[0012] In one embodiment, the chemically tempered aluminosilicate glass has an annealing temperature range of 539°C to 568°C, a softening temperature range of 701°C to 751°C, and a transformation temperature range of 531°C to 588°C.
[0013] In one embodiment, the thickness of the soda-lime glass is c, and the thickness of the chemically tempered aluminosilicate glass is d, satisfying 1.81≤c / d≤2.14.
[0014] In one embodiment, the thickness of the soda-lime glass is 2mm to 3mm, and the thickness of the chemically tempered aluminosilicate glass is 1mm to 1.4mm.
[0015] In one embodiment, the soda-lime glass comprises the following raw materials: SiO2 70wt%~73wt%, Al2O3 0.5wt%~1wt%, Na2O 13wt%~15wt%, MgO 3wt%~4wt%, and CaO 8wt%~10wt%.
[0016] In one embodiment, the adhesive layer comprises at least one of polyvinyl butyral, ethylene vinyl acetate, acrylic resin, urethane resin, polyethylene terephthalate, and cyclic olefin polymer.
[0017] In one embodiment, the following steps are included:
[0018] The soda-lime glass is stacked with the chemically tempered aluminosilicate glass;
[0019] Heating softens the soda-lime glass and the chemically tempered aluminosilicate glass, and then bends them into a predetermined shape;
[0020] After cooling, the soda-lime glass and the chemically tempered aluminosilicate glass are separated; and
[0021] The cooled soda-lime glass, the adhesive layer, and the chemically tempered aluminosilicate glass are sequentially stacked and then hot-pressed together to prepare the laminated glass.
[0022] In one embodiment, the temperature of the hot pressing is 640°C to 660°C, and the processing time is 46s to 65s.
[0023] Compared with traditional technologies, the present invention has the following advantages:
[0024] This invention optimizes the raw materials of aluminosilicate glass, resulting in aluminosilicate glass with thermal properties similar to soda-lime glass, both of which can be bent into the same shape when heated. By combining the aforementioned aluminosilicate glass with soda-lime glass, this invention significantly reduces the overall thickness and weight of laminated glass, achieving the requirements of lightweight and safety in automotive glass. Attached Figure Description
[0025] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0026] Figure 1 This is a cross-sectional schematic diagram of a laminated glass according to an embodiment of the present invention;
[0027] Figure 2 This is a schematic diagram of the cross-section of the glass before and after bending according to an embodiment of the present invention.
[0028] Explanation of reference numerals in the attached figures: 11, soda-lime glass; 12, chemically tempered aluminosilicate glass; 13, adhesive layer. Detailed Implementation
[0029] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to limit the invention. Unless otherwise specifically stated, all raw materials, reagents, instruments, and equipment used in this invention are commercially available or can be prepared by existing methods.
[0031] In this invention, numerical intervals (i.e., numerical ranges) are involved. Unless otherwise specified, the selected numerical distributions within the aforementioned numerical intervals are considered continuous, and include the two endpoints (i.e., the minimum and maximum values) of the numerical range, as well as every value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints. In this document, this is equivalent to directly listing every integer. For example, if t is an integer selected from 1 to 10, it means that t is any integer selected from the group of integers consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10. Furthermore, when multiple ranges are provided to describe features or characteristics, these ranges can be merged. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges to which they are included.
[0032] Unless otherwise specified, the temperature parameters in this invention can be either constant temperature treatment or variations within a certain temperature range. It should be understood that the constant temperature treatment allows temperature fluctuations within the precision range controlled by the instrument. Fluctuations are permitted within ranges such as ±5℃, ±4℃, ±3℃, ±2℃, and ±1℃.
[0033] Some embodiments of the present invention provide a laminated glass comprising, in sequence, soda-lime glass, an adhesive layer, and chemically tempered aluminosilicate glass, wherein the thickness of the chemically tempered aluminosilicate glass is less than the thickness of the soda-lime glass; the difference in annealing temperature between the chemically tempered aluminosilicate glass and the soda-lime glass is -16°C to 16°C, the difference in softening temperature is -25°C to 25°C, and the difference in transformation temperature is -25°C to 25°C.
[0034] Chemically tempered aluminosilicate glass is obtained by tempering aluminosilicate glass. The aluminosilicate glass comprises the following raw materials: SiO2 55wt%~66wt%, Al2O3 9wt%~15wt%, Na2O 11wt%~16wt%, K2O 4wt%~8wt%, MgO 1wt%~5wt%, B2O3 1wt%~6wt%, and ZrO2 0.2wt%~2wt%; wherein, the mass percentage of Al2O3 is a, the sum of the mass percentages of K2O and B2O3 is b, and 1.24≤a / b≤1.67.
[0035] Understandably, the difference in annealing temperature between chemically tempered aluminosilicate glass and soda-lime glass can be any specific value between -16℃ and 16℃, such as -16℃, -15℃, -14℃, -13℃, -12℃, -11℃, 10℃, -9℃, -8℃, -7℃, -6℃, -5℃, -4℃, -3℃, -2℃, -1℃, 0, 1℃, 2℃, 3℃, 4℃, 5℃, 6℃, 7℃, 8℃, 9℃, 10℃, 11℃, 12℃, 13℃, 14℃, 15℃, or 16℃.
[0036] The difference in softening point temperature between chemically tempered aluminosilicate glass and soda-lime glass can be any specific value between -25℃ and 25℃, such as -25℃, -24℃, -23℃, -22℃, -21℃, 20℃, -19℃, -18℃, -17℃, -16℃, -15℃, -14℃, -13℃, -12℃, -11℃, 10℃, -9℃, -8℃, -7℃, -6℃, -5℃, -4℃, -3℃, -2℃, -1℃, 0, 1℃, 2℃, 3℃, 4℃, 5℃, 6℃, 7℃, 8℃, 9℃, 10℃, 11℃, 12℃, 13℃, 14℃, 15℃, 16℃, 17℃, 18℃, 19℃, 20℃, 21℃, 22℃, 23℃, 24℃, or 25℃.
[0037] The transition temperature difference between chemically tempered aluminosilicate glass and soda-lime glass can be any specific value between -25℃ and 25℃, such as -25℃, -24℃, -23℃, -22℃, -21℃, 20℃, -19℃, -18℃, -17℃, -16℃, -15℃, -14℃, -13℃, -12℃, -11℃, 10℃, -9℃, -8℃, -7℃, -6℃, -5℃, -4℃, -3℃, -2℃, -1℃, 0, 1℃, 2℃, 3℃, 4℃, 5℃, 6℃, 7℃, 8℃, 9℃, 10℃, 11℃, 12℃, 13℃, 14℃, 15℃, 16℃, 17℃, 18℃, 19℃, 20℃, 21℃, 22℃, 23℃, 24℃, or 25℃.
[0038] exist Figure 1 In the example shown, the laminated glass comprises soda-lime glass 11, an adhesive layer 13, and chemically tempered aluminosilicate glass 12 stacked sequentially.
[0039] In this invention, the mass percentage of SiO2 is "55wt%~66wt%", which can be the minimum and maximum value of the range 55wt%~66wt%, as well as every value between the minimum and maximum value. Specifically, it includes, but is not limited to, the point values in the embodiments and the following point values: 55wt%, 56wt%, 57wt%, 58wt%, 59wt%, 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, or 65wt%; or any range consisting of any two of these values, such as 55wt%~60wt%.
[0040] SiO2 is a major component of the glass framework. As a primary raw material for glass, it helps reduce the coefficient of thermal expansion and improves the strength and chemical stability of the glass. When the SiO2 content is too low, the mechanical strength and weather resistance of the glass deteriorate, and the coefficient of thermal expansion increases. When the SiO2 content is too high, the melting temperature rises, and defects such as bubbles and inclusions are easily generated, which is detrimental to industrial production. Therefore, this invention controls the SiO2 mass percentage to be 55wt%~66wt%.
[0041] In some alternative embodiments, the mass percentage of SiO2 is 57 wt% to 62 wt%. Further, the mass percentage of SiO2 is 61.2 wt%.
[0042] In this invention, the mass percentage of Al2O3 is "9wt%~15wt%", which can be the minimum and maximum value of the range of 9wt%~15wt%, as well as every value between the minimum and maximum value. Specifically, it includes, but is not limited to, the point values in the embodiments and the following point values: 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, or 15wt%; or any range of any two of these values, such as 9wt%~12wt%.
[0043] Al2O3 is beneficial for improving the structural strength of glass, promoting the integrity of the glass network, enhancing the chemical stability, elastic modulus, and hardness of glass, and free oxygen reacts with Al. 3+ The formation of glass-forming bodies [AlO4] creates larger void channels in the glass's network structure, which facilitates alkali metal ion exchange, resulting in maximum compressive stress and compressive stress depth. In aluminosilicate glasses, excessively high Al2O3 content increases glass viscosity, raises melting temperature, and complicates industrial production; conversely, excessively low Al2O3 content significantly reduces the ion exchange depth during chemical strengthening. Therefore, this invention controls the mass percentage of Al2O3 to be 9wt%~15wt%.
[0044] In some alternative embodiments, the mass percentage of Al2O3 is 12.5 wt% to 15 wt%. Further, the mass percentage of Al2O3 is 14.2 wt%.
[0045] In this invention, the mass percentage of Na2O is "11wt%~16wt%", which can be the minimum and maximum value of the range of 11wt%~16wt%, as well as every value between the minimum and maximum value. Specifically, it includes, but is not limited to, the point values in the embodiments and the following point values: 11wt%, 11.5wt%, 12wt%, 12.5wt%, 13wt%, 13.5wt%, 14wt%, 14.5wt%, 15wt%, 15.5wt%, or 16wt%; or any range consisting of any two of these values, such as 10wt%~12wt%.
[0046] Na₂O is a network exogenous substance that promotes the melting of glass raw materials and enhances chemical strengthening. Excessive Na₂O content reduces the weather resistance and stability of the glass; conversely, insufficient Na₂O content hinders glass melting and reduces the strength of chemical strengthening. Therefore, this invention controls the Na₂O mass percentage to be between 11 wt% and 16 wt%.
[0047] In some alternative embodiments, the mass percentage of Na2O is 13.4 wt% to 16 wt%. Further, the mass percentage of Na2O is 13.4 wt%.
[0048] In this invention, the mass percentage of K2O is "4wt%~8wt%", which can be the minimum and maximum value of the range 4wt%~8wt%, as well as every value between the minimum and maximum value. Specifically, it includes, but is not limited to, the point values in the embodiments and the following point values: 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, or 8wt%; or any range of any two of these values, such as 4wt%~6wt%.
[0049] K₂O and Na₂O have similar properties. Adding both K₂O and Na₂O to the glass composition simultaneously can improve the high-temperature melting and refining of the glass and promote chemical strengthening through the mixed alkali effect. However, if the K₂O content is too high, the ion exchange capacity of the glass will decrease, and the coefficient of linear expansion will increase. Therefore, this invention controls the mass percentage of K₂O to be 4wt%~8wt%.
[0050] In some alternative embodiments, the mass percentage of K2O is 6.5 wt% to 7.5 wt%. Further, the mass percentage of K2O is 6.8 wt%.
[0051] In this invention, the mass percentage of MgO is "1wt%~5wt%", which can be the minimum and maximum value of the range of 1wt%~5wt%, as well as every value between the minimum and maximum value. Specifically, it includes, but is not limited to, the point values in the embodiments and the following point values: 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, or 5wt%; or any range of any two of these values, such as 1wt%~3wt%.
[0052] As an alkaline earth metal oxide, MgO helps lower the glass melting temperature and reduce the tendency for glass crystallization, while also increasing the elastic modulus of glass and inhibiting crack formation. However, if the content is too high, it will increase the coefficient of linear expansion of the glass; if it is too low, it will increase the viscosity of the glass melt. Therefore, this invention controls the mass percentage of MgO to be 1wt%~5wt%.
[0053] In some alternative embodiments, the mass percentage of MgO is 1.6 wt% to 3.7 wt%. Further, the mass percentage of MgO is 1.6 wt%.
[0054] In this invention, the mass percentage of B2O3 is "1wt%~5wt%", which can be the minimum and maximum value of the range of 1wt%~5wt%, as well as every value between the minimum and maximum value. Specifically, it includes, but is not limited to, the point values in the embodiments and the following point values: 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, or 5wt%; or any range of any two of these values, such as 1wt%~3wt%.
[0055] B2O3 is a glass forming agent and flux, which can lower the glass liquidus temperature, softening point temperature, and coefficient of linear expansion, while improving the thermal properties of glass during chemical strengthening and bending processes. However, excessive addition to the glass can reduce the ion exchange capacity of the glass surface. Therefore, this invention controls the mass percentage of B2O3 to be 1wt%~5wt%.
[0056] In some alternative embodiments, the mass percentage of B2O3 is 1 wt% to 2 wt%. Further, the mass percentage of B2O3 is 1.7 wt%.
[0057] In this invention, the mass percentage of ZrO2 is "0.2wt%~2wt%", which can be the minimum and maximum value of the range of 0.2wt%~2wt%, as well as every value between the minimum and maximum value. Specifically, it includes, but is not limited to, the point values in the embodiments and the following point values: 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, or 2wt%; or any range consisting of any two of these values, such as 0.5wt%~1.2wt%.
[0058] ZrO2 can improve the chemical stability of glass, increase its surface hardness, resist crack formation and propagation, and enhance its ion exchange rate, thus making it more scratch-resistant. It is an essential component of glass raw materials. However, excessive ZrO2 content can significantly increase the melting temperature of glass. Therefore, this invention controls the ZrO2 mass percentage to be 0.2wt%~2wt%.
[0059] In some alternative embodiments, the mass percentage of ZrO2 is 1.1 wt% to 1.7 wt%. Further, the mass percentage of ZrO2 is 1.1 wt%.
[0060] In some optional examples, the aluminosilicate glass comprises the following raw materials: SiO2 57wt%~62wt%, Al2O3 12.5wt%~15wt%, Na2O 13.4wt%~16wt%, K2O 6.5wt%~7.5wt%, MgO 1.6wt%~3.7wt%, B2O3 1wt%~2wt%, and ZrO2 1.1wt%~1.7wt%.
[0061] In one alternative example, the aluminosilicate glass comprises the following raw materials: 61.2 wt% SiO2, 14.2 wt% Al2O3, 13.4 wt% Na2O, 6.8 wt% K2O, 1.6 wt% MgO, 1.7 wt% B2O3, and 1.1 wt% ZrO2.
[0062] This invention controls the mass percentages of Al2O3, K2O, and B2O within a specific range, namely 1.24 ≤ a / b ≤ 1.67, which can reduce the softening point of aluminosilicate glass, increase chemical compressive stress and ion exchange depth, thereby meeting the requirements of automotive glass for impact resistance and scratch resistance.
[0063] Understandably, the high proportion of Al2O3 in aluminosilicate glass can make the glass structure more compact and increase its softening point. Using chemically tempered aluminosilicate glass as the inner layer of laminated glass has at least the following advantages: light weight; excellent mechanical properties; thermal properties similar to soda-lime glass 11; and the ability to be heated and bent into the same shape as soda-lime glass 11.
[0064] In some of these alternative examples, the constituent materials of the aluminosilicate glass satisfy 1.51 ≤ a / b ≤ 1.67. Further, the constituent materials of the aluminosilicate glass satisfy a / b = 1.67.
[0065] The chemically tempered aluminosilicate glass 12 of the present invention has excellent mechanical and thermal properties, and is easy to bond with soda-lime glass 11 during hot bending.
[0066] In some specific examples, the difference in annealing temperature between the above-mentioned chemically tempered aluminosilicate glass 12 and the above-mentioned soda-lime glass 11 can be -4℃~4℃, -3℃~3℃, -2℃~2℃, or -1℃~1℃.
[0067] In some specific examples, the difference in softening point temperature between the above-mentioned chemically tempered aluminosilicate glass 12 and the above-mentioned soda-lime glass 11 can be -4℃~4℃, -3℃~3℃, -2℃~2℃, or -1℃~1℃.
[0068] In some specific examples, the difference in transition temperature between the above-mentioned chemically tempered aluminosilicate glass 12 and the above-mentioned soda-lime glass 11 can be -4℃~4℃, -3℃~3℃, -2℃~2℃, or -1℃~1℃.
[0069] In some embodiments, the chemically tempered aluminosilicate glass 12 has an annealing temperature range of 539°C to 568°C, a softening temperature range of 701°C to 751°C, and a transformation temperature range of 531°C to 588°C.
[0070] In some embodiments, the annealing temperature range of the soda-lime glass 11 is 544°C to 553°C, the softening temperature range is 719°C to 726°C, and the transformation temperature range is 556°C to 563°C.
[0071] Specifically, by adjusting the raw materials of aluminosilicate glass, the annealing point temperature, softening point temperature, and transition point temperature of aluminosilicate glass can be optimized.
[0072] In some embodiments, the thickness of the soda-lime glass 11 is c, and the thickness of the chemically tempered aluminosilicate glass 12 is d, satisfying 1.81 ≤ c / d ≤ 2.14. Optionally, the thickness ratio of the soda-lime glass 11 to the chemically tempered aluminosilicate glass 12 is 2.0 to 2.14. More optionally, the thickness ratio of the soda-lime glass 11 to the chemically tempered aluminosilicate glass 12 is 2.07.
[0073] Understandably, the thickness ratio of soda-lime glass 11 and chemically tempered aluminosilicate glass 12 is controlled within a specific range so that both can be bent into the same shape.
[0074] In some embodiments, the thickness of the soda-lime glass 11 is 2 mm to 3 mm, and the thickness of the chemically tempered aluminosilicate glass 12 is 1 mm to 1.4 mm.
[0075] In some specific examples, the thickness of the adhesive layer 13 is 0.36 mm to 0.4 mm. Optionally, the thickness of the adhesive layer 13 is 0.38 mm.
[0076] Understandably, by controlling the thickness ratio, annealing temperature difference, softening temperature difference, and transition temperature difference of soda-lime glass 11 and chemically tempered aluminosilicate glass 12 within the aforementioned specific ranges, the two layers of glass can be simultaneously heated and bent into the same shape, allowing them to fit together tightly.
[0077] When the aforementioned laminated glass is used to manufacture automotive glass, the thicker soda-lime glass 11 is placed on the outside of the car, while the thinner chemically tempered aluminosilicate glass 12 is placed on the inside. This makes the glass less prone to breakage when the car is subjected to a heavy impact, ensuring the mechanical properties of the outer glass of the car.
[0078] In some specific examples, the soda-lime glass 11 mentioned above comprises the following raw materials: SiO2 70wt%~73wt%, Al2O3 0.5wt%~1wt%, Na2O 13wt%~15wt%, MgO 3wt%~4wt%, and CaO 8wt%~10wt%.
[0079] In some specific examples, the adhesive layer 13 comprises at least one of polyvinyl butyral (PVB), ethylene vinyl acetate, acrylic resins, urethane resins, polyethylene terephthalate, and cyclic olefin polymers.
[0080] Some embodiments of the present invention also provide a method for preparing laminated glass, comprising the following steps S10 to S40.
[0081] S10: Provide the above-mentioned raw materials for silicate glass to prepare silicate glass;
[0082] S20: Chemically tempering silicate glass to obtain chemically tempered aluminosilicate glass 12;
[0083] S30: Sodium-calcium glass 11 is stacked with the above-mentioned chemically tempered aluminosilicate glass 12, heated to soften the sodium-calcium glass and chemically tempered glass, and bent into a predetermined shape; and
[0084] S40: After cooling, the soda-lime glass 11 is separated from the above-mentioned chemically tempered aluminosilicate glass 12. The cooled soda-lime glass 11, the adhesive layer 13 and the chemically tempered aluminosilicate glass 12 are stacked in sequence and hot-pressed to prepare laminated glass.
[0085] In some embodiments, step S10 involves preparing silicate glass using methods S11 to S13.
[0086] S11: Provide the above-mentioned raw materials for silicate glass, mix them, and prepare a mixture;
[0087] S12: Melting the mixture to obtain an aluminosilicate glass matrix; and
[0088] S13: Anneal the aluminosilicate glass matrix to obtain aluminosilicate glass.
[0089] In some of these examples, in step S12, the melting temperature is 1550℃~1630℃ and the melting time is 6h~10h.
[0090] In some of these examples, in step S13, the annealing temperature is 630℃~700℃ and the time is 12h~24h.
[0091] In some embodiments, in step S20, the chemical tempering solution is molten KNO3, the treatment temperature is 390℃~425℃, and the treatment time is 3h~8h.
[0092] In some embodiments, in step S30, the heating temperature is 640°C to 660°C, and the heating time is 46s to 65s.
[0093] In some implementations, in step S30, the predetermined shape can be arc-shaped, trapezoidal, or any other arbitrary shape, depending on the application scenario of the laminated glass.
[0094] In some embodiments, in step S40, the temperature of hot pressing is 640°C to 660°C, and the processing time is 46s to 65s.
[0095] In some other embodiments of the present invention, a glass article is provided, comprising the above-described laminated glass or laminated glass prepared by the above-described method for preparing laminated glass.
[0096] The aforementioned glass products possess advantages such as excellent mechanical properties and thinness. They can achieve vehicle lightweighting while meeting automotive safety performance requirements.
[0097] The present invention will be further described below with reference to specific embodiments and comparative examples, but these should not be construed as limiting the scope of protection of the present invention.
[0098] Example 1:
[0099] (1) Preparation of chemically tempered aluminosilicate glass 12:
[0100] a) Provide the required raw materials according to the glass composition raw materials shown in Table 1. The total weight of the raw materials is 800g. Put all the raw materials into the mixer and mix for 30 minutes to obtain the mixture.
[0101] b) Pour the mixture into a platinum-rhodium crucible, melt it at 1550℃~1630℃ for 6~10h, and then clarify and homogenize it at 1530℃~1620℃ for 4h~8h.
[0102] c) Pour the molten glass into a stainless steel mold and anneal it at 630℃~700℃ for 12h~24h, then cool it to room temperature to obtain aluminosilicate glass.
[0103] d) The prepared aluminosilicate glass is cut into slices of 300*300*(1mm~2mm) using a wire cutting machine. Then, it is subjected to coarse grinding, ordinary cleaning, fine grinding, ultrasonic cleaning, CNC edge grinding and chamfering, and polishing. The finished glass slices are placed in molten KNO3 at 390℃~425℃ for chemical tempering for 3h~8h to obtain chemically tempered aluminosilicate glass 12.
[0104] e) The physical and chemical properties of the glass samples were tested: the coefficient of thermal expansion (30℃~300℃) was determined using a German Netzsch DIL-402PC horizontal dilatometer at a heating rate of 5℃ / min; the compressive stress (CS) and compressive stress layer depth (DOL) of the chemically tempered glass surface were determined using an FSM-6000LE surface stress meter; the softening point temperature (Ts) and transition point temperature (Tg) of the glass were determined according to standards ASTM C-336 and ASTM C-338; the viscosity was determined using a high-temperature viscometer, and the melting temperature (Tm) and annealing point temperature (Ta) were calculated according to the Vogel-Fulcher-Tamann formula; the ring-on-ring (ROR) strength of the glass surface was determined using a glass bending strength tester (Dongguan Pusaite PT-307A) at a test speed of 10mm / min, an upper indenter diameter of 32mm, and a lower indenter diameter of 16mm.
[0105] Examples 2-24:
[0106] It is basically the same as Example 1, except that the glass composition raw materials are different, as shown in Tables 1-3.
[0107] Table 1
[0108]
[0109] Table 2
[0110]
[0111] Table 3
[0112]
[0113] Comparative Examples 1-4:
[0114] It is basically the same as Example 1, except that the glass composition raw materials are different, as shown in Table 4.
[0115] Table 4
[0116]
[0117] This invention optimizes the proportions of the raw materials used to prepare aluminosilicate glass, resulting in a glass with a linear expansion coefficient (30℃~300℃) of 94.5×10⁻⁶. -7 / ℃~103.5×10 -7 The aluminosilicate glass exhibits a softening point of 701℃~751℃ (softening point refers to the temperature at which the glass viscosity is 107.65 dPa·s), an annealing point of 539℃~568℃, and a temperature transition point of 531℃~588℃. These thermal properties allow for easy bonding with soda-lime glass during hot bending. After chemical tempering, the aluminosilicate glass exhibits a surface compressive stress of 713.42 MPa~898.39 MPa, a compressive stress layer depth of 27.36 μm~41.33 μm, and a ROR strength range of 413 N~1678 N. Its mechanical properties are significantly superior to traditional soda-lime glass, and it is also thinner.
[0118] In Comparative Examples 1 and 2, the Al₂O₃ / (K₂O+B₂O₃) ratios were 2.44 and 3.10, respectively, significantly higher than 1.67. The softening points of the prepared aluminosilicate glasses were 759℃ and 763℃, respectively, which differed greatly from the softening point of soda-lime glass 11, potentially making bonding between them impossible. Furthermore, the relatively large Al₂O₃ / (K₂O+B₂O₃) ratio in the comparative documents significantly reduced the compressive stress and ROR strength of the aluminosilicate glass.
[0119] In Comparative Example 3, the mass percentage of Al2O3 was 17.5 wt%, and the softening point of the prepared aluminosilicate glass was 778 °C, which may not be compatible with soda-lime glass 11; and the compressive stress and ROR strength were reduced.
[0120] In Comparative Example 4, the K2O mass percentage was 3.5 wt%, and the stress layer depth was relatively low, only 26.43 μm.
[0121] The above results show that by improving and optimizing the constituent raw materials and controlling the mass percentage of each raw material within a specific range, the present invention can prepare aluminosilicate glass with small thickness, excellent mechanical properties and excellent thermal properties.
[0122] Example 25:
[0123] Sodium-calcium glass 3 as shown in Table 5 is provided as sodium-calcium glass 11, with a thickness of 2.0 mm; aluminosilicate glass prepared in Example 23 is provided as aluminosilicate glass, with a thickness of 1.1 mm; the intermediate bonding layer 13 is made of PVB and has a thickness of 0.38 mm.
[0124] Table 5
[0125]
[0126] Flat soda-lime glass 11 and aluminosilicate glass were stacked and fixed on a refractory annular film. The initial heating temperature was set to 450℃~490℃, and increased at a rate of 5℃ / min. The temperature was then raised to 640℃~660℃ and held for 46s~65s to soften the soda-lime glass 11 and aluminosilicate glass. The glass was then bent by gravity into an arc shape roughly consistent with the supporting surface. After cooling, the soda-lime glass 11 and aluminosilicate glass were temporarily separated. The shapes of the glass before and after bending are shown below. Figure 2 As shown. After bending, the aluminosilicate glass is chemically tempered. The chemical tempering solution is molten KNO3, the treatment temperature is 390℃~425℃, and the treatment time is 3h~8h, to obtain chemically tempered aluminosilicate glass 12.
[0127] Subsequently, the bent soda-lime glass 11, the adhesive layer 13, and the chemically tempered aluminosilicate glass 12 are sequentially stacked and then hot-pressed together to obtain the following... Figure 1 The laminated glass shown. The hot pressing step includes: pressing at 1.0MPa~1.9MPa in an autoclave while maintaining at 100℃~150℃ for 45min~80min.
[0128] Examples 26-28, Comparative Examples 5-6:
[0129] The steps are basically the same as in Example 25, except that the soda-lime glass 11 and the chemically tempered aluminosilicate glass 12 are different, as shown in Table 6.
[0130] Table 6
[0131]
[0132] As shown in Table 6, in Examples 25-28, the thickness ratio of soda-lime glass 11 and chemically tempered aluminosilicate glass 12 is controlled between 1.81 and 2.14. During hot bending, the two can be well bonded with a bonding gap of less than 0.01 mm, and the impact resistance of the laminated glass is greater than 0.27 J.
[0133] In Comparative Example 5, the thickness ratio of soda-lime glass 11 to chemically tempered aluminosilicate glass 12 is 1.4, and the difference in their softening point temperatures is 30°C. During hot bending, the gap between the two layers of glass is 0.5 mm, and the laminated glass has weak impact resistance.
[0134] In Comparative Example 6, the thickness ratio of soda-lime glass 11 to chemically tempered aluminosilicate glass 12 is 2.3, and the difference in their annealing temperatures is 21°C. During hot bending, the gap between the two layers of glass is 0.4 mm, and the laminated glass has weak impact resistance.
[0135] This invention combines soda-lime glass 11 of varying thicknesses with chemically tempered aluminosilicate glass 12 to prepare laminated glass. Specifically, the soda-lime glass 11 on the exterior of the vehicle is selected to be 2mm-3mm thick, while the chemically tempered aluminosilicate glass 12 on the interior of the vehicle is selected from the aluminosilicate glass improved in this invention. Without compromising the mechanical properties of the laminated glass, the overall thickness of the laminated glass is significantly reduced, thereby achieving vehicle lightweighting while maintaining safety.
[0136] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0137] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A laminated glass, characterized in that, The glass comprises, in sequence, soda-lime glass, an adhesive layer, and chemically tempered aluminosilicate glass, wherein the thickness of the chemically tempered aluminosilicate glass is less than the thickness of the soda-lime glass; the thickness of the soda-lime glass is c, and the thickness of the chemically tempered aluminosilicate glass is d, and the following condition is met: 1.81 ≤ c / d ≤ 2.
14. The difference in annealing temperature between the chemically tempered aluminosilicate glass and the soda-lime glass is -16℃ to 16℃, the difference in softening temperature is -25℃ to 25℃, and the difference in transformation temperature is -2℃ to 15℃. The chemically tempered aluminosilicate glass is obtained by tempering aluminosilicate glass, which is composed of the following raw materials: SiO2 55wt%~66wt%, Al2O3 9wt%~15wt%, Na2O 11wt%~16wt%, K2O 4wt%~8wt%, MgO 1wt%~5wt%, B2O3 1wt%~6wt%, and ZrO2 0.2wt%~2wt%; wherein, the mass percentage of Al2O3 is a, the sum of the mass percentages of K2O and B2O3 is b, and 1.24≤a / b≤1.67; The soda-lime glass is composed of the following raw materials: SiO2 70wt%~73wt%, Al2O3 0.5wt%~1wt%, Na2O 13wt%~15wt%, MgO 3wt%~4wt%, and CaO 8wt%~10wt%.
2. The laminated glass according to claim 1, characterized in that, The aluminosilicate glass is composed of the following raw materials: SiO2 57wt%~62wt%, Al2O3 12.5wt%~15wt%, Na2O 13.4wt%~16wt%, K2O 6.5wt%~7.5wt%, MgO 1.6wt%~3.7wt%, B2O3 1wt%~2wt%, and ZrO2 1.1wt%~1.7wt%.
3. The laminated glass according to any one of claims 1 to 2, characterized in that, The mass percentage of Al2O3 is a, the sum of the mass percentages of K2O and B2O3 is b, and 1.51 ≤ a / b ≤ 1.
67.
4. The laminated glass according to any one of claims 1 to 2, characterized in that, The thickness of the soda-lime glass is c, and the thickness of the chemically tempered aluminosilicate glass is d, and the condition 2≤c / d≤2.14 is satisfied.
5. The laminated glass according to any one of claims 1 to 2, characterized in that, The difference in annealing temperature between the chemically tempered aluminosilicate glass and the soda-lime glass is -4℃ to 4℃; and / or The difference in softening point temperature between the chemically tempered aluminosilicate glass and the soda-lime glass is -4℃ to 4℃; and / or The temperature difference between the transition point of the chemically tempered aluminosilicate glass and the soda-lime glass is -2℃ to 4℃.
6. The laminated glass according to any one of claims 1 to 2, characterized in that, The annealing temperature range of the chemically tempered aluminosilicate glass is 539℃~568℃, the softening temperature range is 701℃~751℃, and the transformation temperature range is 531℃~588℃.
7. The laminated glass according to claim 1, characterized in that, The thickness of the soda-lime glass is 2mm to 3mm, and the thickness of the chemically tempered aluminosilicate glass is 1mm to 1.4mm.
8. The laminated glass according to any one of claims 1 to 2, 7, characterized in that, The adhesive layer comprises at least one of polyvinyl butyral, ethylene vinyl acetate, acrylic resin, urethane resin, polyethylene terephthalate, and cyclic olefin polymer.
9. The method for preparing laminated glass according to any one of claims 1 to 8, characterized in that, Includes the following steps: The soda-lime glass is stacked with the chemically tempered aluminosilicate glass; Heating softens the soda-lime glass and the chemically tempered aluminosilicate glass, and then bends them into a predetermined shape; After cooling, the soda-lime glass and the chemically tempered aluminosilicate glass are separated. as well as The cooled soda-lime glass, the adhesive layer, and the chemically tempered aluminosilicate glass are sequentially stacked and then hot-pressed together to prepare the laminated glass.
10. The method for preparing laminated glass according to claim 9, characterized in that, The temperature of the hot pressing is 640℃~660℃, and the processing time is 46s~65s.
Citation Information
Patent Citations
Boron aluminum silicate glass and preparation method thereof
CN116102255A